Tinjauan Geometrik Jalan Raya Pada Titik-Titik Rawan Kecelakaan (Blackspots) Di Kota Semarang - Denis Bramedio Herlambang; Rosie Febri Febri Setyadi; Rudatin Ruktiningsih (G-SMART, 2017)
This study is based on traffic accidents in Indonesia which increased from year to year, theincrease of the accident rate resulted in the loss of material or casualties. Frequent accidentsare classified as blackspots (accident-prone points). Then to minimize the blackspot, there is aneed to study the safety of traffic more deeply, one of the efforts is to conduct a road geometricreview. In the geometric overview of the highway there are horizontal alignments and verticalalignments as the main points of discussion, where horizontal alignments discuss the speed,bend length, stop visibility, side free areas, bend extension and super elevation. While thevertical alinemen discuss about the cleverness, and vertical arch. Analysis of horizontalalignment and vertical alignment based on RSNI 2004 criteria. The results of this study indicatethat there are some discussion of horizontal alignment and vertical alignment that is not inaccordance with the criteria of RSNI 2004, the discussion includes the length of the curve, thestop visibility, and the side free area for alinemen horizontal, and vertical curvatures andvertical alignments.